LEPTIN DETERMINATION AND SERUM LEVELS IN ADULT ALPACAS WITH DIFFERENT BODY CONDITION - Enciso H., Marco (2007)
The aim of this study was to determine the presence of leptin in adults alpacas, in order to quantify leptin values for these animals, and to relate them with body condition. For this purpose, 36 non pregnant and non nursing female adult alpacas were used. They were divided in two groups according to body condition (BC): G1: BC <3.0 and G2: BC>3.0, using the 1 to 5 scale (1: emaciate, 5: obese). Blood samples by jugular venipunction to obtain serum were taken. Serum samples were maintained at -20 ºC until analysis. The leptin determination was carried out by the radioimmunoassay technique (RIA). The mean of leptin concentration was 17.23 ± 0.81 ng/ml. Values for G1 were 18.14 ± 1.12 ng/ ml and for G2. were 16.32 ± 1.15 ng/ml, without statistical differences between groups. The results showed that the leptin hormone is also present in alpacas.